Peran Teknologi Informasi Dalam Pembelajaran Daring Di Era Pandemi Covid 2019 - Jey Fhiter Wassalam, Ockhy; Alfina; Yudha Prawira, Tresna (Universitas Aisyah Pringsewu, 2022)
The pandemic situation requires the Indonesian people to spend more time at home, limitingtheir mobility and interaction with each other to break the chain of virus transmission. Peopleare asked to work from home, worship at home, and study from home. Various digitaltechnologies, applications and digital platforms that support learning are helpful during apandemic like this. Compared to face-to-face learning, of course, online learning has itsdrawbacks, but it also has advantages. This study uses a literature review research method relatedto the role of technology in online learning during the Covid-19 period. Information Technologyemphasizes the implementation and processing of data such as capturing, transmitting, storing,retrieving, manipulating or displaying data using electronic technology devices such ascomputers and gadgets. Learning is essentially a transactional communication that is reciprocalboth between educators and students and students with students and the learning environment inan effort to achieve learning objectives. From the meaning of learning, there is a core meaningthat learning must contain elements of information technology, thus the technology needed inlearning